2022
DOI: 10.1021/acs.langmuir.1c02518
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Coating-Less Aluminum Superhydrophobic Gradient for Spontaneous Water Droplet Motion Using One-Step Laser-Ablation

Abstract: Nature shows various approaches to create superhydrophobicity, such as the lotus leaf, where the superhydrophobic (SHPB) surface arising from its hierarchical surface consists of random microscale bumps with superimposed nanoscale hairs. Some natural systems, such as the hydrophilic silk of some spider's webs, even allow the passive transport of water droplets from one part of a surface to another by creating gradients in surface tension and Laplace pressure. We look to combine both ideas and replicate the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…In a condensing environment, the condensate droplets moved at a microscale from a HPB line to a HPL channel; at the 10, pattern viii, using laser etching, which promoted a nanoscale line-edge roughness supporting a SHPB wetting state at one end of the gradient. 129 As first reported in ref 105, this style of gradient also displayed bimodal transport of liquid droplet depending upon the surface contamination. When the surface was cleaned, the Wenzel wetting state was promoted, resulting in spontaneous spreading.…”
Section: Topographically Engineeredsupporting
confidence: 74%
See 3 more Smart Citations
“…In a condensing environment, the condensate droplets moved at a microscale from a HPB line to a HPL channel; at the 10, pattern viii, using laser etching, which promoted a nanoscale line-edge roughness supporting a SHPB wetting state at one end of the gradient. 129 As first reported in ref 105, this style of gradient also displayed bimodal transport of liquid droplet depending upon the surface contamination. When the surface was cleaned, the Wenzel wetting state was promoted, resulting in spontaneous spreading.…”
Section: Topographically Engineeredsupporting
confidence: 74%
“…Misiiuk et al prepared a gradient type, as shown in Figure , pattern viii, using laser etching, which promoted a nanoscale line-edge roughness supporting a SHPB wetting state at one end of the gradient . As first reported in ref , this style of gradient also displayed bimodal transport of liquid droplet depending upon the surface contamination.…”
Section: Passive Liquid-transport Mechanismsmentioning
confidence: 73%
See 2 more Smart Citations
“…, all proved to be suitable for multiple wettability materials, whether they themselves are hydrophobic or not. 29,39–43 Analogously, gradient topography also affects microbial adhesion to the matrix, which provides an easy-to-manipulate way to guide cell behaviours, such as cell adhesion, cell migration, cell proliferation, and stem cell differentiation. As indicated in Fig.…”
Section: Gradient Materialsmentioning
confidence: 99%